2007
DOI: 10.1507/endocrj.k06-225
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Plasma Leptin Levels and Fetal Growth Restriction

Abstract: Abstract. Leptin is a satiety hormone secreted from the adipose tissue and human placenta. We previously demonstrated that severe preeclampsia up-regulated leptin mRNA expression in the placenta and elevated maternal plasma leptin concentrations. Preeclampsia is frequently related to generation of small for gestational age (SGA) infant especially in cases with severe preeclampsia. However, it is still controversial whether the increase in maternal plasma leptin levels is associated with fetal growth restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
(44 reference statements)
3
45
0
2
Order By: Relevance
“…We observed a significant difference of leptin level between IUGR and normal growth group in PE patients; these data are consistent with a recent report [34] and suggested that placental insufficiency might affect leptin production in placenta. Moreover, the placental hypoxic condition, which results from inadequate trophoblast invasion of maternal spiral arteries in PE [3,4], has been demonstrated to cause not only the abnormal production of angiogenic factors, such as VEGF, PlGF, sFlt-1 and sEng [6][7][8][9][10][11], but also placental leptin production [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…We observed a significant difference of leptin level between IUGR and normal growth group in PE patients; these data are consistent with a recent report [34] and suggested that placental insufficiency might affect leptin production in placenta. Moreover, the placental hypoxic condition, which results from inadequate trophoblast invasion of maternal spiral arteries in PE [3,4], has been demonstrated to cause not only the abnormal production of angiogenic factors, such as VEGF, PlGF, sFlt-1 and sEng [6][7][8][9][10][11], but also placental leptin production [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Humans have interstitial implantation compared with the superficial form with fewer invasive trophoblasts seen in Old World monkeys (46). CCK has been shown to regulate leptin levels (47), and leptin expression levels have been shown to change in the obstetrical syndromes of preeclampsia and intrauterine growth retardation (48). GH2 also increases its expression in patients with preeclampsia (49).…”
Section: Resultsmentioning
confidence: 99%
“…An inverse relation between leptin level and infant birth weight has been observed in some, though not all, previous studies. [21][22][23][24] Of note, Verhaeghe and colleagues found that, compared with glucose, insulin, adiponectin and tumour necrosis factor-α, leptin was the mediator that was most strongly (and negatively) associated with birth weight. 23 Placental dysfunction has been suggested as a unifying mechanism underlying both fetal growth restriction and elevated maternal leptin levels (through increased placental production of leptin), al though this model remains speculative.…”
Section: Discussionmentioning
confidence: 99%